Chronic ventricular assist device support: surgical innovation. (May 2016) - Rojas, Sebastian V.; Hanke, Jasmin S.; Haverich, Axel; Schmitto, Jan D.
Abstract : Purpose of review: Ventricular assist device (VAD) therapy is currently one of the fastest-developing fields in cardiac surgery. Consistently improved technology, research, and gain of clinical experience have established VADs as an important option for the treatment of congestive heart failure. During the past year, novel devices and less invasive surgical procedures have been revolutionizing this field. The purpose of this manuscript is to review these innovations with special emphasis on device-related surgery. Recent findings: Device miniaturization has enabled less invasive VAD surgery, excluding the need for full sternotomy. Recent data show that intrahospital survival rates following less invasive VAD implantation are surpassing 90%. Secondly, two new devices, Heartmate 3 and MVAD, are being applied and tested for clinical application. In this context, the Heartmate 3 CE mark study recently concluded with excellent outcomes and without any pump thrombosis or device malfunctions. Summary: The first clinical results of the newest generation of VADs are very promising compared with old-generation devices. Furthermore, less invasive surgery is becoming a standard for the implantation, exchange, or explantation of left VADs. The joint venture of improved technology and innovative surgical techniques will push this field forward to even better outcomes and reduced complication rates.